Rising Food Prices: A Perspective from North Africa - Priego, Alberto (UNISCI Discussion Papers, 2014)
Over the last 4 years the World has suffered at least three food crises. To find an accurate explanation we need to pay attention to a set of different causes (economic, environmental, financial, technical, political and social). In Northern Africa, food crisis have been the trigger for the social and political struggle that we label as Arab Spring. This article will analyse the causes of the rise of food prices and its consequences for the North African population.
Keywords: Food prices; Maghreb; Food security; Arab Spring.